The importance of contextualization in pedagogical practice (Research, Society and Development, 2019)
This article aims to discuss the importance of contextualization in pedagogical practice, enabling the reflection on meaningful learning, which occurs through the relationship between students' personal experiences and the school curriculum. Recognizing that learning should be a dialogical process, the concept is reaffirmed that it is through dialogue that the teacher knows the student, identifies their thinking and, only then, can reflect on the changes necessary to favor their development. Through bibliographic research it was found that when students can relate the contents studied in the classroom with situations experienced in everyday life, the results are more satisfactory in terms of learning.